Comparison of five 2nd-generation supraglottic airway devices for airway management performed by novice military operators - Henlín, Tomáš; Sotak, Michal; Kovaricek, Petr; Tyll, Tomas; Balcárek, Lukáš; Michalek, Pavel (BioMed research international, 2015)
OBJECTIVES: Five different second-generation supraglottic airway devices, ProSeal LMA, Supreme LMA, i-gel, SLIPA, and Laryngeal Tube Suction-D, were studied. Operators were inexperienced users with a military background, combat lifesavers, nurses, and physicians. METHODS: This was a prospective, randomized, single-blinded study. Devices were inserted in the operating room in low light conditions after induction of general anesthesia. Primary outcome was successful insertion on the first attempt while secondary aims were insertion time, number of attempts, oropharyngeal seal pressure, ease of insertion, fibre optic position of device, efficacy of ventilation, and intraoperative trauma or regurgitation of gastric contents. RESULTS: In total, 505 patients were studied. First-attempt insertion success rate was higher in the Supreme LMA (96%), i-gel (87.9%), and ProSeal LMA (85.9%) groups than in the Laryngeal Tube Suction-D (80.6%) and SLIPA (69.4%) groups. Insertion time was shortest in the Supreme LMA (70.4 ± 32.5 s) and i-gel (74.4 ± 41.1 s) groups (p < 0.001). Oropharyngeal seal pressures were higher in the Laryngeal Tube Suction-D and ProSeal LMA groups than in other three devices. CONCLUSIONS: Most study parameters for the Supreme LMA and i-gel were found to be superior to the other three tested supraglottic airway devices when inserted by novice military operators.
Keywords: Equipment Design; dospělí; zajištění dýchacích cest; Laryngeal Masks; klinické kompetence; vojenské lékařství; Female; analýza selhání vybavení; ozbrojené síly; Airway Management; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; lidé; dvojitá slepá metoda; Clinical Competence; Military Personnel; Treatment Outcome; Aged, 80 and over; Equipment Failure Analysis; Double-Blind Method; Male; laryngální masky; Aged; Czech Republic; Young Adult; Military Medicine; Česká republika; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; design vybavení; Middle Aged; Humans